Comparative evaluation of antimicrobial effectiveness of probiotic milk and fluoride mouthrinse on salivary Streptococcus mutans counts and plaque scores in children - An in vivo experimental study - Raju Umaji Patil; Persis P Dastoor; Maitreyee P Unde (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of the study was to compare the effectiveness of probiotic milk and fluoride mouthwash on salivary Streptococcus mutans (SM) counts and plaque index (PI) scores in children. Materials and Methods: Thirty children of 8-13 years with zero decayed, missing, and filled teeth (dmft)/DMFT were randomly divided into two equal groups of 15 each; baseline saliva samples were collected, and plaque scores were recorded. Group A received probiotic milk and Group B received fluoride mouthwash for 7 days, and then, saliva samples were collected for colony counting, and plaque scores were recorded on the 8th day. Study Design: This was a double-blind experimental in vivo study and randomized sample selection. Results: The results showed that there was statistically significant reduction in both salivary SM counts and plaque scores in both the groups after 7 days period. Intergroup comparison showed that there was no statistically significant difference between the two groups (i.e., both groups are equally effective in caries reduction). Conclusion: Probiotic milk was as effective as fluoride mouthwash in reducing SM counts and PI scores.